Bond positions, expectations, and the yield curve - Monika Piazzesi; Martin Schneider (Federal Reserve Bank of Atlanta, 2008)
This paper implements a structural model of the yield curve with data on nominal positions and survey forecasts. Bond prices are characterized in terms of investors' current portfolio holdings as well as their subjective beliefs about future bond payoffs. Risk premia measured by an econometrician vary because of changes in investors' subjective risk premia that are identified from portfolios and subjective beliefs but also because subjective beliefs differ from those of the econometrician. The main result is that investors' systematic forecast errors are an important source of business cycle variation in measured risk premia. By contrast, subjective risk premia move less and more slowly over time.
Keywords: E4; E5; G1; 330; expectations; surveys; interest rates; portfolio choice; asset positions; term structure; yield curve